Cardiocirculatory responses to human passive walking-like leg movement in the standing posture - Hisayoshi Ogata (Japanese Society of Physical Fitness and Sports Medicine, 2016)
Passive walking-like leg movement in the standing posture (PWM) has been used to activate neural mechanisms responsible for generating gait movement and to prevent disuse syndrome including muscle atrophy, bone mass loss and joint contracture as a rehabilitation tool for individuals with gait disturbance. However, circulatory responses to PWM have not been fully determined, despite the potential risk of orthostatic intolerance from standing posture. Quiet standing (QS) causes a decrease in blood volume in the ventricles due to the pooling of blood in the lower extremities and subsequent decrease in stroke volume. On the other hand, cardiac contractility and heart rate increase to maintain cardiac output due to enhancement of sympathetic nerve activity. The enhancement of cardiac activity is linked to vasovagal responses characterized by bradycardia and the drop in arterial blood pressure and symptoms such as pallor, lightheadedness, hyperventilation and blurred vision, especially in young individuals. In addition, QS can cause orthostatic hypotension due to loss of sympathetic control of the heart and vasculature in individuals with cervical spinal cord injury. Vasovagal response and orthostatic hypotension may lead to syncope. However, PWM has been shown to induce a decrease in cardiac activity compared to that during QS in young individuals and a large increase in arterial blood pressure in individuals with cervical spinal cord injury, suggesting that PWM reduces the risks of vasovagal responses and orthostatic hypotension and, consequently, syncope. The efficacy and safety of PWM suggests that PWM is a useful tool for rehabilitation in individuals with gait disturbance.